PERUBAHAN PERILAKU MASYARAKAT DALAM HUKUM KELUARGA ISLAM: STUDI TENTANG PERNIKAHAN DINI DI NAGARI TIGO JANGKO - Muhammad Yusuf; Zainuddin Zainuddin (UIN Mahmud Yunus Batusangkar, 2023)
The main problem in this thesis is how people's behavior changes in Islamic family law in Tigo Jangko Nagari, cases of early marriage before and after the establishment of customary regulations in Tigo Jangko Nagari, and the factors that influence changes in Tigo Jangko people's behavior towards early marriage. This type of research used field research using qualitative methods. The primary data sources used were Niniak Mamak, KAN, Wali Nagari, KUA, community leaders and Alim Ulama. Secondary data sources include through other people or documents. The results of the research found were cases of early marriage before the existence of customary regulations, many people who had early marriages, there were 16 cases. Then, with the implementation of customary rules, cases of early marriage have decreased to 5 cases. There are several kinds of community factors that change behavior regarding this matter, including the factor of being aware of the law, the factor of being afraid of being locked up in a traditional prison, and the factor of being embarrassed to be in a traditional prison. With these factors, changes in people's behavior change to the good, from the many acts of early marriage to the lack of early marriage.